THE ROLE OF PARENTS AND TEACHER IN OVERCOMING BEHAVIOR THE ROLE OF PARENT AND TEACHER IN COMMITTING NIRADIC AND NIRETIC BEHAVIOR IN STUDENTS - Purba, Rafindo; Fadzuani Damanik, Abdul Khalik; Syuhada, Yasin; Lubis, Rozy Abdullah; Simbolon, Hendra Gunawan (Proceeding International Seminar of Islamic Studies, 2023)
The family is the first place for children to receive education, namely in their daily social life. So that in this case the role of parents is very decisive in the formation of attitudes and behavior of children so that they grow and develop into children of noble character. In the formation of a child's morals, cooperation between the family (parents) and the school (teacher) is needed. The formation of student morals takes place gradually and continuously between parents and teachers. Teachers have part of the responsibility of parents to provide education, when children are delegated to teachers at school. It doesn't matter which family the child is bestowed on. Teachers are parents of students at school. As parents at school, teachers should be responsible for the development of their students both in terms of cognitive, affective and psychomotor. Especially for Islamic Religious Education Teachers (PAI) who have a duty not only to transfer knowledge but also to provide teaching and guidance related to student morals. With regard to good morals or examples, Allah SWT has provided an overview of the morals of the Prophet Muhammad SAW. Because in life, a human being from birth always acts and acts, thinks, feels, feels and relates to other people.